Applications of xylochemistry from laboratory to industrial scale. Issue 14 (29th June 2020) - Groß, Jonathan; Kühlborn, Jonas; Opatz, Till
Abstract : Xylochemicals, their utilisation in total synthesis and industrial scale production as well as their advantages over petroleum-based chemicals are highlighted. Abstract : Xylochemicals and their utilisation in total synthesis and industrial applications are highlighted in this review. This class of chemicals consists of bio-based molecules or building blocks derived from renewable feedstocks like plant-biomass, lignocellulose as well as waste-streams. The advantages over petroleum-based chemicals are presented with the aid of specific examples ranging from the total synthesis of natural products, relevant industrial applications to the exploitation of CO2 as a C1 feedstock. This review contributes to the trend of a "greener" and a more sustainable chemistry.